Shekhavati Kshetra Ki Jal Dharohar Par Lage Etihasik Lekhan ke Srot : Ek Abhilekhiya Addhyan - Har Lal Singh; Dr. Manju Gupta (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
Shekhawati has been a subordinate province of Jaipur state of Rajputana in India. Established and ruled by Rao Shekha and his descendants, this region has a distinct rich cultural traditions and history. Apart from archaeological and literary material, this is available in abundance in the area in the form of travelogues and folklore. Shekhawati has a distinct tradition of creating water heritage in the context of historical cultural traditions. Which includes wells, stepwells, ponds, ponds, ponds, dams, ditches etc. of the area. Although the literary wealth of writing history of Shekhawati's water heritage is available only in small quantities. But the most reliable records of archaeological importance and historical writing are located in the walls, pillars, stones and umbrellas of this water heritage. On the basis of which, there is immense help in writing not only the water heritage but also the entire history of Shekhawati. These inscriptions on water heritage are inscribed on stones, rocks, plaques and Kirti Stambhs. Which are strong witnesses to provide information about the history, art, culture, society, religion and traditions related to that water heritage. Inscriptional sources written on rocks and umbrellas are found at Ramsagarji well located in Sunyunu. Articles written on Chadwan are found in Sonagari Stepwell located in Khandela. The inscriptions written on the stone tablets are Antaramji's Johad in Ramgarh, Ghadwa Johad in Fatehpur, Manavsagar Pond in Sikar, Harinarayanji's Pond in Paukh, Seth Pannalal Shah's Pond in Khetri, Saledipura Dam, Bahuji, Maji Sa and Draupadi ki stepwells in Khandela, etc. Are found in places. In which many important and bias-free information about the history of water heritage like the creator, year of construction, purpose of construction etc. is available. In the stone slab located on the left side of Saledipura, a list of kings of Amarsar and Khandela is given, from Sodhadev of Narwar branch of Kachhwahas to Udaykaranji of Amer state and his sons and grandsons, which is very important in the history writing of Rajputana